"Music is life": Identity, challenge, and passion in the occupational patterns of male young adult rock musicians. Issue 2 (2nd April 2020) - King, Brooke E.; Pierce, Doris
ABSTRACT: This qualitative study examined the occupational experiences of young adult rock musicians using first-hand accounts solicited through semi-structured interviews. Participants included nine male rock musicians aged 19 to 35 who actively participated in an income-generating rock band. A grounded theory approach was used for data analysis and interpretation. Participation in a rock band was conceptualized as a dynamic process between identifying as a musician, facing challenges, and meeting challenges, which either led musicians to persevere or to discontinue engagement in the band. Results challenge stereotypes associated with rock band participation and contribute to understanding the connection between occupational engagement and motivation. Band participation as a co-occupation and relationships between technology and occupational engagement are also discussed.